2019
DOI: 10.15666/aeer/1705_1126111272
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adaptation Measures on Climate Change. A Case of Small-Scale Maize Farmers in the North-West Province of South Africa

Abstract: Adaptation to climate change varies according to regions, it could be effective in relation to people and their locations. Adaptation to climate change in sub-Saharan Africa is different from that of developed countries, as resources are limited. This study was conducted in Ngaka Modiri Molema District Municipality in North West Province of South Africa. This study examined the determinants of climate change adaptation strategies among rural farmers' households in the study area. A total number of 346 question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…The accumulation of experience possessed by a farmer determines the awareness of climate change, besides age also plays a significant role with respect to the farmer’s experience, or otherwise. Equally, according to Oduniyi (2018), Ndambiri et al (2012) and Deressa et al (2008), age was found to be statistically significant to climate change awareness. Ajuang et al (2016) also assert that age significantly affects climate change awareness.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The accumulation of experience possessed by a farmer determines the awareness of climate change, besides age also plays a significant role with respect to the farmer’s experience, or otherwise. Equally, according to Oduniyi (2018), Ndambiri et al (2012) and Deressa et al (2008), age was found to be statistically significant to climate change awareness. Ajuang et al (2016) also assert that age significantly affects climate change awareness.…”
Section: Resultsmentioning
confidence: 87%
“…Ironically, just as agricultural production contributes to climate change, yet it is also affected by it. In Sub-Saharan countries, South Africa inclusive, the impact of climate change, as reported by Oduniyi (2018), has reflected on financial capital, and which is attributed to low profit and low cooperative finance. According to Grain South Africa (GSA, 2015), maize industry is one of the largest supply of food production that yields about 25 to 33 per cent of the country total gross agricultural production, and this form the staple food for the majority.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this result is that the knowledge and experience of the landowners determine the adoption of natural resources management and the level of adaptive capacity. This was supported by [23], who reported that landownership is likely to influence adoption if the innovation requires investments tied to the land. Figure 2 shows the predictive margin graph of adaptive capacity used by pasture-based livestock farmers in the study area in the face of climate-related events.…”
Section: Resultsmentioning
confidence: 81%
“…Eigenvectors and eigenvalues exist in pairs and every eigenvector has a corresponding eigenvalue. An eigenvector is a direction while an eigenvalue is a number that shows how much variance there is in the data in that direction [23].…”
Section: Empirical Modelmentioning
confidence: 99%
“…A list of small-scale maize farmers in the municipalities was obtained from the Department of Agriculture, Forestry, and Fisheries (DAFF). The Raosoft sample-size calculator was used to determine the sample size from the population of maize farmers in the study area [16]. This sample-size calculator takes into account the margin of error, confidence level, and response distribution.…”
Section: Population Sampling Procedure and Sample Sizementioning
confidence: 99%